WHEN CULTURE MEETS RELIGION: THE MULUDAN TRADITION IN THE KA-NOMAN SULTANATE, CIREBON, WEST JAVA - Mohamad Yusuf (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
This article is based on a fundamental question, what is the relationship between practicing the Muludan tradition and seeking of power by the Royal family of the Kanoman Sultanate in Cirebon? The Muludan is a tradition conducted by the Royal family, and thousands of people participate in this tradition. This article is aimed to analyze the extent of which the Royal family uses Muludan tradition to regain their political power as they had in the past. Our participatory research shows that the Muludan tradition could be defined as a religious-cultural system. This is not only a religious ritual but also a cultural tradition. On the one hand this tradition is done primarily based on the knowledge, beliefs, norms and moral values of religious teachings. People participating in this tradition believe that they would gain God blessing (Ngalap Berkah) and Shafa’at as cited by the Quran and the Hadith. On the other hand, this tradition involves cultural tradition that has been practiced by the local people since long time ago. This research also found that the Royal family fails to use this tradition to gain political power as they intend to do. This tradition could mainly effectively be implemented in terms of the socio-cultural relationship between the Sultan and the followers. Political power, the Royal family aims to gain through conducting the Muludan tradition, does not significantly happen. Key words: The Muludan Tradition, Power Relationship, Religious Identity, and the Kanoman Sultanate